2015
DOI: 10.1017/s1366728915000243
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in very young children's English acquisition in China: Internal and external factors

Abstract: This study assesses the impact of internal and external factors on very young EFL learners in an instructional setting. 71 child English learners in China (onset age: 2;0 -5;6) were involved: their receptive vocabulary, productive vocabulary and receptive grammar were taken as outcome variables, and age of onset, short-term memory, nonverbal intelligence, English input quantity and quality, English use, and maternal English level were taken as predictive variables. Multiple regression analyses, verified by Bay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
79
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(94 citation statements)
references
References 48 publications
(97 reference statements)
14
79
0
1
Order By: Relevance
“…By contrast, in Extremaduran rural schools, parents have a lower sociocultural status, with fewer university degrees, higher unemployment rates and a greater percentage of mothers staying at home. This confirms some of the findings by Sun et al (2015) who found that the situation at home is of critical importance in the attainment of students.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…By contrast, in Extremaduran rural schools, parents have a lower sociocultural status, with fewer university degrees, higher unemployment rates and a greater percentage of mothers staying at home. This confirms some of the findings by Sun et al (2015) who found that the situation at home is of critical importance in the attainment of students.…”
Section: Discussionsupporting
confidence: 91%
“…In close connection to child studies, it is the mother's level of English in Chinese EFL children (cf. Sun et al, 2015), which also seems to be the case with Spanish EFL learners. Rica Goiricelaya and González de San Román (2012), in an analysis of EFL students in their last years of Spanish Secondary Education (age 13-16), found a positive effect on the proficiency level of the students related to the educational level of the mother and the job status of the father, the oral skill being the one most affected by this variable (Rica Goiricelaya & González de San Román, 2012, p. 26).…”
Section: Motivationmentioning
confidence: 65%
See 2 more Smart Citations
“…Research on young learners has shown clear differences in their use of a second language (L2) and in their attainment in L2 learning in foreign language contexts. These differences may be due to many factors, both internal and external to the language learner (e.g., Sun, Steinkrauss, Tendeiro, & de Bot, ; Unsworth, Hulk, & Marinis, ). An important factor that has not received sufficient attention in L2 research is the linguistic distance between the learners’ first language (L1) and their L2, despite the common acknowledgment that the number of hours of instruction required will differ depending on the relatedness of the languages.…”
Section: Introductionmentioning
confidence: 99%